Five 3D Co(ii)-MOFs constructed from 5-(2-methylimidazol-1-yl) isophthalic acid and different bis(imidazole) ligands and one of their derivatives as an efficient electrocatalyst for ORR. Issue 45 (4th November 2022) - Yang, Ming-Xing; Yan, Rong-Zhi; Chen, Li-Juan; Lin, Shen
Abstract : Five 3D Co(II)-MOFs constructed from 5-(2-methylimidazol-1-yl) isophthalic acid and different bis(imidazole) ligands and one of their derivatives as an efficient electrocatalyst for ORR. Abstract : In this work, four different bis(imidazole) ligands, namely 1, 4-bis(1-imidazolyl)benzene (bib), 4, 4′-bis(1-imidazolyl)biphenyl (bibp), 1, 4-bis (imidazol-1-ylmethylene)benzene) (bimb) and 4, 4′-bis(imidazol-1-yl)diphenyl ether (bidpe), were used as the second ligand to give rise to the structural diversity of a coordination polymer based on the cobalt-miipa (H2 miipa = 5-(2-methylimidazol-1-yl) isophthalic acid) system. In compound 1, miipa 2− coordinates to Co(ii ) atoms to form the Co-miipa 3D network. On introducing linear bis(imidazole) ligands with different lengths and rigidities into the Co(ii )-miipa system, the obtained compounds 2–4 form similar three-fold interpenetrating 3D MOFs constructed from the Co(ii )-miipa layers pillared by bis(imidazole) ligands. While introducing the V-shaped half-flexible bis(imidazole) ligands, the obtained compound 5 exhibits a 2D double-layered network built from the Co(ii )-miipa 1D quadrangular prism linked by the bis(imidazole) ligand. Each 2D double layer is further interlocked with two neighboring ones to produce an interesting 3D framework. Significantly, CoNC-5 derived from a mixture of dicyandiamide (DCD) and compound 5 with a low void volume shows a superior electrocatalytic performance for the oxygen reduction reaction. The E onset (0.974 V) and E 1/2 (0.830 V) of CoNC-5 in O2 -saturated 0.1 M KOH at 1600 rpm and 5 mV s −1 are superior to those of Pt/C (0.968 and 0.799 V). The J L value of CoNC-5 ( J L = 5.29 mA cm −2 ) is higher than that of Pt/C (5.09 mA cm −2 ).